2014
DOI: 10.1093/cid/ciu660
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors for Homo- and Heterosubtypic Antibodies Against Influenza A Virus

Abstract: Background. The effectiveness of trivalent influenza vaccination has been confirmed in several studies. To date, it is not known whether repeated exposure and vaccination to influenza promote production of cross-reactive antibodies. Furthermore, how strains encountered earlier in life imprint the immune response is currently poorly understood.Methods. To determine the prevalence for human homo-and heterosubtypic antibody responses, we scrutinized serum samples from 305 healthy volunteers for hemagglutinin-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Overall, these observations highlight the importance of “original antigenic sin” in protection against zoonotic influenza viruses. They also reaffirm that seasonal influenza virus infection or vaccination can elicit heterosubtypic antibodies against antigenically similar zoonotic influenza viruses [108, 146149]. …”
Section: Protective Immunity Against Zoonotic Influenza Virusesmentioning
confidence: 82%
“…Overall, these observations highlight the importance of “original antigenic sin” in protection against zoonotic influenza viruses. They also reaffirm that seasonal influenza virus infection or vaccination can elicit heterosubtypic antibodies against antigenically similar zoonotic influenza viruses [108, 146149]. …”
Section: Protective Immunity Against Zoonotic Influenza Virusesmentioning
confidence: 82%
“…Our findings raise questions about whether seasonal influenza vaccination might boost broadly-protective anti-HA responses (27) or alter imprinting from natural infection in IAV-naïve children. By exposing IAV-naïve children simultaneously to group 1 (H1N1) and group 2 (H3N2) antigens, vaccination might confer dual imprinting to both HA groups, or prevent strong imprinting against either HA group—or it could have no effect beyond delaying the age of imprinting via the first natural infection.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, primary exposure to H5N1 or H7N9 can activate HA stem-specific reactivities induced by previous infection by H1 or H3, respectively (12,13,26). Indeed, others have suggested that heterosubtypic antibodies might attenuate disease from other IAV strains and may be imprinted to some degree by childhood exposure, though their serological assays provided no ability to detect or predict actual patterns of protection relevant to H5N1 and H7N9 in human populations (27). …”
Section: Antigenic Seniority Across Influenza Subtypesmentioning
confidence: 99%
“…It is suspected that some influenza vaccines, such as the H1/pdm09 vaccine, promote production of cross-reactive antibodies, whereas original antigenic sin (OAS), that is the preferential expansion of memory B cell clones from the initial immune response [2][3][4], most likely restricts their generation. We could recently show that repetitive vaccination of HIVnegative individuals generally stimulates homo and heterosubtypic responses [5].…”
Section: Introductionmentioning
confidence: 99%